RETRACTED: ALLERGENIC EXTRACTS STANDARDIZATION: PROSPECTS FOR THE FUTURE - V. V. Smirnov; D. O. Bokov (Сеченовский вестник, 2013)
RETRACTED ARTICLEThis article reviews the methodological basic procedures of the allergenic extracts standardization protocols used for the allergen-specific immunotherapy in the world nowadays. The comparative analysis of the normative documents regulating the basic technological stages of allergenic extracts production was carried out. The data concerning the production and quality control of this biological drugs group was generalized. It is shown that the method of tandem mass spectrometry of high resolution combined with high performance liquid chromatography could be advantageously employed in the study area.